From the Transmission of knowledge to the digital transition: the great challenge of universities (Journal of Philosophy Culture and Political Science, 2019)
The article reveals some challenges facing the system of national education in the Republic of Kazakhstan in the field of digitization of academic communication. The study of this problem is inevitable in the era of universal global digital communication in the academic world. According to the objectives of the state program «Digital Kazakhstan» approved by the Government of the Republic of Kazakhstan № 827 12.12.2017: «Industry 4.0, one of the drivers of digital transformation industry, is the concept of production, where additional value is provided by the integration of physical objects, processes and digital technologies, in which physical processes are monitored in real time, decentralized solutions are adopted, as well as the interaction of machines between themselves and people».The national education is one of those fields where digital communication skills need to be implemented at all levels, while at the same time providing the tasks of educating young people, as well as adequate communication with the global academic world in the process of the internationalization of higher education and research. The article is written within the framework of realization of research project «Multidimensional Research of history, problems and prospects of implementation of international educational projects in the Republic of Kazakhstan» on grant financing of the Ministry of education and science of the Republic of Kazakhstan.Key words: Model of national education, internationalization of higher education and science in the Republic of Kazakhstan, democracy, education, John Dewey, International educational projects, digitalization in the Republic of Kazakhstan, academic communication, communication model, University 4.0.